Informed societies : why information literacy matters for citizenship, participation and democracy - Goldstein, Stéphane (Facet Publishing, 2020)
This book explains how and why information literacy can help to foster critical thinking and discerning attitudes, enabling citizens to play an informed role in society and its democratic processes